Energy flows on smallholder farms in the Ethiopian highlands - Gryseels, Guido; Goe, M.R. (1984)
Studies energy flows on typical smallholder farms around Debre Zeit and Debre Berhan in the Ethiopian highlands, describing the farming system resource base and intermediate roles of resources such as animal traction. Discusses energy aspects of the household system and prospects for improvement in energy use, especially with respect to animal traction, fuel consumption, wind energy, solar energy, biogas, thermal and hydroelectric power, and geothermal energy.